Persepsi Masyarakat Kenagarian Lurah Ampalu terhadap Peraturan Bupati Nomor 13 Tahun 2016 tentang Penertiban Orgen Tunggal sebagai Upaya Pendidikan Karakter - Larisman, Larisman; Destuliadi, Destuliadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine how the perception of the community of Ampalu Village Head towards the regent's regulation number 13 of 2016 concerning the regulation of single organs as an effort to educate character. This study uses a quantitative research approach with a descriptive survey method. The study results show that: (1) The public's perception of single organs is a mean value of 29.92, a median of 30.00, a mode of 21, a standard deviation of 6.209, a variance of 38.552, a range of 22, a minimum value of 20, and a maximum of 42. It is known that the average perception of 29.92 is greater than the theoretical mean, so the public's perception of single organs is negative. (2) The public's perception of the regent's regulation is a mean value of 62.32, median of 64.00, mode of 64, standard deviation of 8.985, variance of 80.729, minimum value of 40, and maximum of 80. It is known that the average perception is 62.32. In conclusion, public perception of the regent's regulation is positive. Keywords: Perception, Regent's Regulation, Character Education